Insight into the 1 December 2016 Mw 6.2 Juliaca Earthquake, Southern Peru, by InSAR Observations and Field Investigation - Qingfeng Hu; Weiwei Jia; Jiuyuan Yang; Yanling Zhao (Remote Sensing, 2023)
On 1 December 2016, an Mw 6.2 earthquake characterized by normal faulting occurred in the highlands of the central Andes in southern Peru, marking the region’s largest shallow event. The occurrence of the earthquake provides a significant chance to gain insight into the regional tectonic deformation and the seismogenic mechanism of the shallow normal-faulting earthquake, as well as the regional potential seismic risk. Here, we first utilize Sentinel-1A interferometric synthetic aperture radar (InSAR) data to extract the coseismic and postseismic deformation associated with this earthquake and then determine the detailed coseismic slip and postseismic afterslip distribution of this event. Coseismic modeling results indicate that the coseismic rupture is mainly characterized by normal faulting with some dextral strike-slip components. Most coseismic slip is confined to a depth range of 2–12 km, indicating an obvious slip deficit area in the shallow fault part. Further postseismic modeling reveals that the majority of afterslip is concentrated at depths of 0 to 5.4 km. The relatively shallow postseismic afterslip makes up for the coseismic slip deficit area to some extent. Through a joint analysis of the inversions, seismic data, and regional geology and geomorphology, we infer that the occurrence of this 2016 normal-faulting event is a result of regional gravitational collapse. In addition, we investigate the relationship between the 2016 earthquake and great historical earthquakes near the subduction zone of the central Andes and find that the 2016 event is likely promoted in advance by these events through our calculations of the coseismic and postseismic Coulomb stress changes. Finally, we should pay more attention to the nearby Falla Huaytacucho-Condoroma fault and the western segment of the Vilcanota Fault because of their relatively high stress loading.